Successful Return of Regular Menstrual Flow After Removal of A Huge Cervical Fibroid: A Case Report - Shamim, Shayela; Rouf, A (Journal of Surgical Sciences, 2019)
Fibroids are the commonest benign neoplasm of the uterus and have long been implicated as a cause of complication during pregnancy and delivery. Fibroids arising from uterine cervix constitute only less than 2% of all fibroids and a very large cervical fibroid is even rarer1·2·3. This is case report of pregnancy with a huge cervical fibroid that necessitated caesarean section delivery. This unusually large fibroid (20 x 17 x 16 cm) was grown from the cervix that pushed up the uterine body upward. During initial caesarean operation the surgical team could not ascertain about the origin of the mass and closed the abdomen without remony the man. Subsequent laparotomy three months after caesarean section finally confirmed the diagnosis of the huge cervical fibroid. It was dissected out from the surrounding adhesion followed by end-to-end anastomosis of the gap between uterus and cervix. The postoperative period was uneventful with smooth recovery. The patient was followed up couple of times after discharge and reported to be well with return of her normal menstrual and reproductive function. Journal of Surgical Sciences (2013) Vol. 17 (1) : 58-61